Workforce participation among international medical graduates in the National Health Service of England: a retrospective longitudinal study - Young Ruth; Sibbald Bonnie; Hann Mark (BMC, 2008)
Abstract Background Balancing medical workforce supply with demand requires good information about factors affecting retention. Overseas qualified doctors comprise 30% of the National Health Service (NHS) workforce in England yet little is known about the impact of country of qualification on length of stay. We aimed to address this need. Methods Using NHS annual census data, we calculated the duration of 'episodes of work' for doctors entering the workforce between 1992 and 2003. Survival analysis was used to examine variations in retention by country of qualification. The extent to which differences in retention could be explained by differences in doctors' age, sex and medical specialty was examined by logistic regression. Results Countries supplying doctors to the NHS could be divided into those with better or worse long-term retention than domestically trained doctors. Countries in the former category were generally located in the Middle East, non-European Economic Area Europe, Northern Africa and Asia, and tended to be poorer with fewer doctors per head of population, but stronger economic growth. A doctor's age and medical specialty, but not sex, influenced patterns of retention. Conclusion Adjusting workforce participation by country of qualification can improve estimates of the number of medical school places needed to balance supply with demand. Developing countries undergoing strong economic growth are likely to be the most important suppliers of long stay medical migrants.